2015
DOI: 10.1002/app.42894
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxidized ferulic acid on physicochemical properties of bitter vetch (Vicia ervilia) protein‐based films

Abstract: The aim of the present study was to investigate the effect of oxidized ferulic acid on some physicochemical features of bit-\ud ter vetch protein concentrate-based films. Our results indicate that moisture content, total soluble matter, water vapor permeability, and mechanical resistance values of the films prepared in the presence of oxidized ferulic acid were significantly modified in compari- son with the ones detected with films obtained in its absence. In fact, film moisture content, total soluble matter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Films produced with 4% oTA at different pH values (4 and 9) are also noticeably different, the latter being much rougher, probably because of the higher pH favoring TA oxidation. Increased roughness in protein films was also reported to be promoted by the presence of oxidized ferulic acid …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Films produced with 4% oTA at different pH values (4 and 9) are also noticeably different, the latter being much rougher, probably because of the higher pH favoring TA oxidation. Increased roughness in protein films was also reported to be promoted by the presence of oxidized ferulic acid …”
Section: Resultsmentioning
confidence: 99%
“…Increased roughness in protein films was also reported to be promoted by the presence of oxidized ferulic acid. 36…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The water solubility of the control, FE, and FUV0.32 film was found to be around 40%. The insignificant effect of ferulic addition on water solubility is similar to that reported by (Arabestani et al, 2016). Contrarily, Insaward et al (2015) reported that ferulic acid addition to soy protein film caused a reduction in its water solubility.…”
Section: Water Solubilitysupporting
confidence: 83%
“…Fifty milligram ferulic acid per 100 g OSA‐modified starch was added to the film‐forming solution in order to prepare OSA‐modified starch film containing ferulic acid. The rest of the method was as mentioned in Section 2.3 (Arabestani, Kadivar, Shahedi, Goli, & Porta, ).…”
Section: Methodsmentioning
confidence: 99%